MODULAR RATING SYSTEM OF ASSESSMENT STUDENT KNOWLEDGE (Pedagogy of Higher and Secondary Education, 2022)
In Permjakova Alexander Anatoljevicha and Zelenkovoj Natalia Ivanovny's clause theoretical questions of a modul-rating estimation of knowledge ofpupils of modem school are considered.